Vertical handoff and resource management in heterogeneous wireless networks - Ma, Dong (2013)
The trend of the fourth-generation wireless networks (4G) is the coexistence of hetero-geneous technologies. With an overlay architecture, advantages of different technolo-gies can be well integrated into one system, allowing subscribers to profit the best service anytime and anywhere, i.e., the so-called “always best connected” (ABC). To efficiently integrate heterogeneous networks, several key issues should be investigat-ed. Among them, the most fundamental issue is the interworking architecture, which provides the solution on the platform to combine the overlay networks together. Under different architectures, the integration mechanisms in terms of mobility management, data transmission, quality-of-service (QoS) provision, and security might be quite dif-ferent. The handoff management is another essential aspect for interworking. The handoff between heterogeneous networks is referred to as vertical handoff. Unlike traditional horizontal handoff which is mainly triggered by signal strength, more factors should be considered in a vertical handoff decision, such as monetary cost, network conditions, user preference, and so on. The objective of a vertical handoff will be no longer the continuous connection but the best connection. On the other hand, because the radio resources in the interworking system can be viewed as being shared in a resource pool, the complete and efficient use of these pooled resources is also an important topic.